2013
DOI: 10.1099/jmm.0.054262-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of enteroaggregative Escherichia coli and its virulence-related genes in a case–control study among children from north-eastern Brazil

Abstract: Enteroaggregative Escherichia coli (EAEC) is an important agent that causes endemic and epidemic diarrhoeal diseases worldwide. Several EAEC virulence-related genes (VRGs) have been described but their role in the clinical outcome of infection is not completely defined. This study investigated the prevalence of EAEC and potential associations of its VRGs with risk of or protection from diarrhoeal diseases in children from urban communities in north-eastern Brazil. The case-control study included 166 children, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
86
6
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 75 publications
(108 reference statements)
13
86
6
3
Order By: Relevance
“…Therefore, we infer the importance of evaluating the grade according to the thickness of the scum layer formed. Results show that 65 (26 strains) harbored one of the AAF genes, which indicates that the frequency of EAEC strains harboring AAF genes in our study is higher than that found in other countries (22,25). The classification of aggR-positive E. coli as EAEC in this study might have contributed to this high figure.…”
Section: Discussioncontrasting
confidence: 45%
“…Therefore, we infer the importance of evaluating the grade according to the thickness of the scum layer formed. Results show that 65 (26 strains) harbored one of the AAF genes, which indicates that the frequency of EAEC strains harboring AAF genes in our study is higher than that found in other countries (22,25). The classification of aggR-positive E. coli as EAEC in this study might have contributed to this high figure.…”
Section: Discussioncontrasting
confidence: 45%
“…Nevertheless, despite EAEC implications in several clinical scenarios, the molecular epidemiology of this pathogen remains unclear. This is mostly due to the heterogeneity of strains, and even though several virulence genes have been identified in EAEC, none have shown to be present in all strains (11)(12)(13)(14), making the recognition of truly virulent strains difficult.Several reports suggest that the key step in EAEC pathogenesis is the ability of the pathogen to adhere to and colonize the intestinal tract, which in EAEC prototype strains is facilitated by aggregative adherence fimbriae (AAF), followed by heavy biofilm formation (15-18). Four variants of the AAF major structural subunit have been described so far: AggA (AAF/I), AafA (AAF/II), Agg3A (AAF/III), and Agg4A (AAF/IV), all regulated by the transcriptional activator AggR, situated on the EAEC virulence plasmid pAA (19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Nevertheless, despite EAEC implications in several clinical scenarios, the molecular epidemiology of this pathogen remains unclear. This is mostly due to the heterogeneity of strains, and even though several virulence genes have been identified in EAEC, none have shown to be present in all strains (11)(12)(13)(14), making the recognition of truly virulent strains difficult.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study opted to study a chromosomal gene (aaiC). As shown by Lima et al (2013) the aaiC gene is a good candidate for molecular diagnosis because it has a chromosomal origin and is more prevalent that plasmid genes in EAEC. Our findings for aaiC and aggR revealed that the difference between the molecular diagnosis of chromosomal and plasmid genes was 59 strains positive for aaiC and only 48 for aggR (Table 2).…”
Section: Discussionmentioning
confidence: 99%